Penetrating Macrophage-Based Nanoformulation for Periodontitis Treatment - Yan, Na; Xu, Junchao; Liu, Guolin; Ma, Chao; Bao, Lin; Cong, Yalin; Wang, Ziyao; Zhao, Yuliang; Xu, Weihua; Chen, Chunying (ACS nano, 2022)
Periodontitis is a chronic inflammatory disease caused by the interaction of oral microorganisms with the host immune response. Porphyromonas gingivalis (P.g.) acts as a key mediator in subverting the homeostasis of the local immune system. On the one hand, P.g. inhibits phagocytosis and the killing capacity of immune cells. On the other hand, P.g. increases selective cytokine release, which is beneficial to its further proliferation. Here, we prepared a penetrating macrophage-based nanoformulation (MZ@PNM)-encapsulating hydrogel (MZ@PNM@GCP) that responded to the periodontitis microenvironment. MZ@PNM targeted P.g. via the Toll-like receptor complex 2/1 (TLR2/1) on its macrophage-mimicking membrane, then directly killed P.g. through disruption of bacterial structural integrity by the cationic nanoparticles and intracellular release of an antibacterial drug, metronidazole (MZ). Meanwhile, MZ@PNM interrupted the specific binding of P.g. to immune cells and neutralized complement component 5a (C5a), preventing P.g. subversion of periodontal host immune response. Overall, MZ@PNM@GCP showed potent efficacy in periodontitis treatment, restoring local immune function and killing pathogenic bacteria, while exhibiting favorable biocompatibility, all of which have been demonstrated both in vivo and in vitro.